Axial capacity and ductility of circular UHPC-filled steel tube columns - Guler, Soner; Copur, Alperen; Aydogan, Metin (Emerald, 2013)
This paper presents an experimental study of circular ultra-high-performance concrete-filled steel tube (UHPCFT) columns under monotonic axial compression. Some performance indices, termed concrete contribution ratio (CCR), strength enhancement index (SI) and ductility index (DI), are investigated in relation to the diameter-to-thickness ratio (D/t) of the UHPCFT columns. The axial bearing capacities of the UHPCFT columns obtained from the test results are compared with Eurocode 4, American Concrete Institute, Australian Standards and Architectural Institute of Japan design codes. The test results show that increasing the steel tube thickness from 2·5 mm to 3·65 mm enhances the DI by 69%, but the SI only by 5%. Although the Eurocode 4 design code overestimates the axial bearing capacities of the UHPCFT columns, the American Concrete Institute, Australian Standards and Architectural Institute of Japan codes are conservative.